Pedological aspects in the functioning of spring niches as transition zones between underground and superficial parts of the water cycle in a river basin - Jonczak, Jerzy (Ecological Questions, 2013)
The aim of the study was to characterize the soils of spring niches in the valley of the Jarosławianka River in the context of its functioning in the transition zone between underground and superficial parts of the water cycle in the river basin. Five spring niches, representing different soil types (proper gley soils, peat-like soils, peat-mud soils) were studied. Small-scale relief in nearby water seepages is an important factor, which determined the direction of pedogenesis in spring niches. The relief can enhance or hinder accumulation of organic matter. Specific characteristics of soil-forming environment of spring niches (water surplus and its permanent flow through the soil) are reflected in some chemical properties of the soils (low concentration of active and plant-available forms of N, P and K) and properties of soil organic matter (a low rate of the humification process). Soil organic matter strongly affects the sorption and buffer properties of the soils. Ionic composition of the soil sorption complex is determined by the chemistry of feeding waters. More than 99.3% of total cations are bases, especially calcium.